The role of ultrasound findings in the management of thyroid nodules with atypia or follicular lesions of undetermined significance. (30th October 2013) - Yoo, Won Sang; Choi, Hoon Sung; Cho, Sun Wook; Moon, Jae Hoon; Kim, Kyung Won; Park, Hyo Jin; Park, So Yeon; Choi, Sang Il; Choi, Sung Hee; Lim, Soo; Yi, Ka Hee; Park, Do Joon; et al.
Summary Background Atypia or follicular lesions of undetermined significance (AUS/FLUS) is a broad cytological category in the Bethesda system for classifying thyroid cytology. This study investigated the diagnostic accuracy of ultrasound (US) analysis of thyroid nodules with AUS/FLUS. Patients and Methods Of 5062 subjects with nodules subjected to fine‐needle aspiration cytology (FNACs) at our institution from January 2010 through May 2012, 383 met the Bethesda criteria for AUS/FLUS. After excluding subjects who had a history of thyroid cancer, who only underwent repeat FNA or who underwent no further examinations, we selected 249 subjects who had subsequently undergone a core‐needle biopsy and/or surgery. Of these, 100 were found to have malignant nodules (40·2%), 122 had benign nodules (49%), and 27 had nodules with indeterminate status (10·8%). We compared specific US parameters, including size, location, content, shape, margin, echogenicity, echotexture and calcification across these subject groups. Results Multivariate analysis revealed that malignancy was associated with taller‐than‐wide shape (TDW) (OR = 8·43, P = 0·002), ill‐defined margin (OR = 3·23, P = 0·002) and marked hypoechogenicity. (OR = 3·61, P = 0·001). The specificity and positive predictive values of TDW were 98% and 90·6%, respectively. The specificity and positive predictive values of 'TDW and marked hypoechogenicity' were both 100%. Conclusion US findings play a complementary role in the diagnosis of thyroid nodules with AUS/FLUS. In case of highly suspicious US findings such as 'TDW and marked hypoechogenicity', could be very helpful in the diagnosis of malignancy.